2021
DOI: 10.1111/luts.12395
|View full text |Cite
|
Sign up to set email alerts
|

Chronic psychological stress and lower urinary tract symptoms

Abstract: It is well established that lower urinary tract symptoms (LUTS), particularly urinary urgency and incontinence, cause stress and anxiety for patients. However, there is mounting evidence that the relationship between these two factors is bidirectional and that chronic psychological stress itself can result in the development of symptoms such as urinary frequency, urgency, incontinence, and pelvic pain. This review considers the evidence that such a relationship exists and reviews the literature from clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 109 publications
2
26
1
Order By: Relevance
“…However, we did not find a significant effect in our analyses. Bladder hyperactivity is also a vegetative correlate of anxiety, but we did not find association between BoNT treatment for this indication and decreased incidence of anxiety either 50 . As for saliva production, xerostomia is rather associated with anxiety than sialorrhea 51 .…”
Section: Discussioncontrasting
confidence: 78%
“…However, we did not find a significant effect in our analyses. Bladder hyperactivity is also a vegetative correlate of anxiety, but we did not find association between BoNT treatment for this indication and decreased incidence of anxiety either 50 . As for saliva production, xerostomia is rather associated with anxiety than sialorrhea 51 .…”
Section: Discussioncontrasting
confidence: 78%
“…Moreover, several previous studies described the relationship between psychological stress and the development of abnormal urinary tract signs and symptoms [56,57]. Although few recent reports in the literature showed that COVID-19 infection itself can cause symptoms of urinary tract infection [58][59][60], no study has investigated the association of COVID-19-related psychological distress with urinary tract health.…”
Section: Discussionmentioning
confidence: 99%
“…High-intensity and high-pressure workplaces could potentially lead to the deteriorating physical and mental health of Chinese physicians, especially those in large tertiary medical centers. In addition, due to the COVID-19 pandemic, Chinese doctors are also suffering from higher workload and greater psychological stress ( 31 ), which have been linked to LUTS ( 32 ).…”
Section: Discussionmentioning
confidence: 99%